Impact of Oil and Non-oil Tax Revenue on Economic Growth in Nigeria - Otekunrin, Adegbola Olubukola; Fakile, Samuel Adeniran; Eluyela, Damilola Felix; Onabote, Ademola Andrew; John, Okoye Nonso; Ifeanyichukwu, Sarah (International Journal of Energy Economics and Policy, 2023)
This study examined the impact of oil and non-oil tax revenue on economic growth in Nigeria. few works have covered oil and non-oil taxation and the relationship of petroleum profit tax (PPT), company income tax (CIT), value-added tax (VAT) and custom and excise duties tax (CED) on Real Gross Domestic Product of Nigeria. The study adopted an ex-post facto research design, and data were drawn from the annual reports of Central Bank of Nigeria and Federal Inland Revenue Services publications. Error Correction Model was employed to analyse the data collected after subjecting the series to unit root test and cointegration test. The result of the study showed that PPT with a coefficient of 31.71067 and p-value of 0.0004 and CED with a coefficient of 1.786145 and p-value if 0.0206 had a positive significant relationship with economic growth, while CIT with a coefficient of -14446.50 and p-value of 0.0066 and VAT with a coefficient of -23.33177 and p-value of 0.0001 had a negative significant relationship with economic. The study recommends that taxation be appropriately controlled to boost economic growth, lower inflation, and create jobs in the country. More attention to the channelling PPT and CED revenue collections to infrastructural developments will bring about the economic growth of the country.